Neck and Trunk Muscle Strength in Children With Spinal Muscular Atrophy Is Lower Than in Healthy Controls and Depends on Disease Type - Stępień, Agnieszka; Osiak, Tomasz; Rekowski, Witold; Wit, Andrzej (Frontiers in Neurology, 2021)
Background: Neck and trunk muscle strength and relationship with motor function in individuals with spinal muscular atrophy (SMA) is not investigated well. Information on maximum muscle strength that children with SMA may develop considerably expands the possibilities of assessing the effectiveness of pharmacological treatment methods and therapeutic procedures. This study sought to assess neck and trunk muscle strength in patients with SMA and to compare it with values noted in healthy children. Methods: The study involved 56 individuals with SMA aged 5-16 not treated pharmacologically, including 9 patients with SMA type 1 (SMA1), 27 with SMA type 2 (SMA2) and 20 with SMA type 3 (SMA3). The control group included 111 healthy individuals aged 5-16. Neck and trunk muscle strength was assessed by means of a maximum voluntary isometric contraction method with the use of a handheld digital muscle tester MICROFET2. Moreover, relative strength was also calculated by standardising the maximum voluntary isometric contraction according to body mass. The Kruskal–Wallis test, Mann–Whitney U-test and Spearman's rank correlation were used for statistical analysis. Results: The reliability of the neck and trunk muscle strength measurements with the handheld digital muscle tester was excellent with ICC>0.9. The values of muscle strength in SMA groups were significantly lower than in the control group. The values of relative torque of the neck muscles expressed in percentage values calculated with regard to the control group were at the level of 47.6-51.6% in SMA1 group, 54.8-57.1% in SMA2 group and 80.6-90.3% in SMA3 group. The percentage values for upper and lower trunk muscle strength were at the level of 42.6%-68.4% in SMA1 group, 56.9%-75.4% in SMA2 group and 76.7%-94.8% in SMA3 group. Conclusion: Handheld dynamometry provides reliable measures of neck and trunk muscle strength in SMA children. Neck and trunk muscle strength in children with SMA is lower than in healthy controls and depends on disease type, which confirms the theory based on clinical observations. Further study is needed to investigate the effect of pharmacological treatment on the strength of the neck/trunk muscles, and relationship between neck and trunk muscle strength and motor capabilities.